2021
DOI: 10.20396/bjos.v19i0.8661088
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity associated with tooth loss due to caries?

Abstract: Aim: To investigate the association between obesity, overweight, and tooth loss due to caries among university students of (Federal University of Pelotas) in southern Brazil. Methods: A cross-sectional study with all first-year students who regularly enrolled in the first semester of 2016 who were invited to respond to a self-administered questionnaire contain socioeconomic and demographic; psychosocial; oral health; behavioral questions. The body mass index (BMI) was calculated through the self-reported data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The present study was reported as recommended by the Strobe statement (Strengthening the Reporting of Observational Studies in Epidemiology) for cross-sectional studies. Compete methodology is available elsewhere [11][12][13] .…”
Section: Methodsmentioning
confidence: 99%
“…The present study was reported as recommended by the Strobe statement (Strengthening the Reporting of Observational Studies in Epidemiology) for cross-sectional studies. Compete methodology is available elsewhere [11][12][13] .…”
Section: Methodsmentioning
confidence: 99%